A liquid biopsy for detecting circulating mesothelial precursor cells: A new biomarker for diagnosis and prognosis in mesothelioma - Duong, Bill T.V. (EBioMedicine, 2020)
BACKGROUND: Malignant pleural mesothelioma (MPM) is an aggressive cancer related to asbestos exposure. Early diagnosis is challenging due to generic symptoms and a lack of biomarkers. We previously demonstrated that mesothelial precursor cells (MPC) characterized by mesothelin (MSLN)+CD90+CD34+ could be implicated in the development of mesothelioma after asbestos exposure. Here, we aimed to determine the clinical significance of detecting MPC in blood for early-stage diagnosis and prognosis of mesothelioma. METHODS: Due to the rarity of MPC in blood, it is challenging to identify this cell population using conventional techniques. Hence, we have developed a microfluidic liquid biopsy platform called MesoFind that utilizes an immunomagnetic, mesothelin capture strategy coupled with immunofluorescence to identify rare populations of cells at high sensitivity and precision. To validate our technique, we compared this approach to flow cytometry for the detection of MPC in murine blood and lavage samples. Upon successful validation of the murine samples, we then proceeded to examine circulating MPC in 23 patients with MPM, 23 asbestos-exposed individuals (ASB), and 10 healthy donors (HD) to evaluate their prognostic and diagnostic value. FINDING: MPC were successfully detected in the blood of murine samples using MesoFind but were undetectable with flow cytometry. Circulating MPC were significantly higher in patients with epithelioid MPM compared to HD and ASB. The MPC subpopulation, MSLN+ and CD90+, were upregulated in ASB compared to HD suggesting an early role in pleural damage from asbestos. The MPC subpopulation, MSLN+ and CD34+, in contrast, were detected in advanced MPM and associated with markers of poor prognosis, suggesting a predominant role during cancer progression. INTERPRETATION: The identification of circulating MPC presents an attractive solution for screening and early diagnosis of epithelioid mesothelioma. The presence of different subtypes of MPC have a prognostic value that could be of assistance with clinical decisions in patients with MPM. FUNDING: Princess Margaret Hospital Foundation Mesothelioma Research Fund, Toronto General & Western Hospital Foundation.